A new quantizing insulator soldering technology scheme for microwave module. Issue 4 (28th December 2018) - Tian, Fei‐Fei; Zhou, Ming; Zhang, Jun Zhi
Abstract: A new quantizing technology scheme of insulator soldering was presented comparing with traditional soldering technology using solder paste, based on utilization of solid solder ring and the consideration of insulator mounting hole design on the microwave module shell. The X‐ray test on void ratio of insulator soldering shows that there exists no penetration void and the void ratio is below 5%. According to the leak standard A4 of GJB 548B‐1014.2, the standard leak rate of microwave module after the insulator soldering was below 5 × 10 −9 (Pa·m 3 )/s. After 10 cycles of temperature shock test ranging from −55°C to 125°C, the standard leak rate of microwave module was still below 5 × 10 −9 (Pa·m 3 )/s. In comparison with traditional insulator soldering technology using solder paste, through utilization of solid solder ring and the design of insulator mounting hole, this new technology quantized the soldering of insulator so as to resolve the existing defects of traditional insulator soldering such as solder overflow, high void ratio, shortcut and channel blocking. The quantized insulator sealed soldering technology ensured the reliability, air impermeability, uniformity and beautifulness of soldering meanwhile improved operators' efficiency.